Credit a question of confidence - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Because it is used to pay for the necessary seeds, fertilizer and equipment, money ranks as the most important input for agricultural modernization. And no maffer how you look at it, money often means credit and credit means confidence - mutual...